Perilaku Beresiko di Komunitas Gay: Perspektif Bimbingan dan Penyuluhan Islam di PKBI Kota Semarang - Simpatik Nudia Paradisa (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2021)
Background: This study aims to describe how the efforts implemented by PKBI Semarang City and how the analysis of Islamic Guidance and counselling on PKBI Semarang City in overcoming the dangers of risky behavior in the gay community. Method: This study is a descriptive qualitative study that aims to find out the efforts made by PKBI Semarang City in overcoming the dangers of risky behavior in the gay community, which is then described in the form of a description of words or writings. The data collection techniques used in this study are with observations, interviews, and documentation. Results: PKBI Semarang City has several programs to prevent HIV / AIDS transmission, namely, outreach and assistance, especially key populations such as: WPS, WPS Customers, gay, and Transvestites with preventive materials including (condoms, pelican, KIE). Conducting socialization activities to increase knowledge about STIs and HIV / AIDS Information needs to be done continuously, for example by using the mechanism of weekly meetings. Clinics, to prevent the transmission of HIV / AIDS and detect the presence of HIV / AIDS early, by empowering to always live healthy. PKBI Semarang City has not implemented any full Islamic extension guidance but seen from the form of extension and coaching activities carried out both individually and in groups. In the extension of PKBI Semarang city has a significant influence on the gay community, this is seen from the number of people with HIV / AIDS which decreased compared to the previous year.